Iodine-Catalyzed Synthesis of Fused Polycyclic Heterocycles Containing Pyrazoloquinoline via Povarov Reaction. (7th August 2016) - Zhang, Wen-Ting; Zhang, Mei-Mei; Wang, Xiang-Shan
Abstract : A three components Povarov reaction of aromatic aldehyde, cyclobutanone, and 1 H -indazol-5-amine or 1 H -indazol-6-amine is described, and gives fused polycyclic heterocycles containing pyrazoloquinoline analogue in good yields catalyzed by iodine.